Intelligence Can Grow in All Dimensions: Findings from an Experiment in Latin America - Santander-Urrutia, D (Springer Science and Business Media B.V., 2024)
Computer-based interventions that aim to help students endorse a growth mindset have been designed and tested in high-income countries for a number of years. However, there is no evidence of their effectiveness in middle-income nations. In those studies, students’ growth mindset has traditionally been measured using surveys where students report the extent to which they believe intelligence is fixed or malleable, without linking intelligence with a more specific dimension, such as math or language. In addition, these measurements have been undertaken without distinctions being made between personal ability (“my” intelligence) and more general abilities (everyone’s intelligence). Therefore, by means of a randomized experiment, this study assesses the impact of a single-session online growth-mindset intervention in Chile on distinct measurements of the growth mindset of students (general, personal, and subject-specific), as well as their propensity to seek out challenges. Accordingly, a sample of 248 students was recruited from 9 and 11th grades in three secondary schools, all of whom were randomly assigned to either a treatment or control group. The intervention was found to increase their propensity to seek out challenges and to experience an increase in growth mindset scores in all tested dimensions. No evidence of the heterogeneity of results by gender or prior growth mindset was identified. © Instituto Universitário de Ciências Psicológicas, Sociais e da Vida 2023.